2010
DOI: 10.1182/blood-2010-03-275651
|View full text |Cite
|
Sign up to set email alerts
|

LYL1 activity is required for the maturation of newly formed blood vessels in adulthood

Abstract: The 2 related basic helix loop helix genes, LYL1 and TAL-1 are active in hematopoietic and endothelial lineages. While Tal-1 is essential for both hematopoietic and vascular development, the role of Lyl1 appears to be distinct as deficient mice are viable and display modest hematopoietic defects. Here, we reveal a role for Lyl1 as a major regulator of adult neovascularization. Tumors implanted into Lyl1-deficient mice showed higher proliferation and angiogenesis, as evidenced by enlarged lumens, reduced pericy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 45 publications
6
44
0
Order By: Relevance
“…We previously reported that lack of LYL1 affects the maturation of newly formed blood vessels in adult mice and reduces active Rap1 in ECs (32). Here, we completed our analysis of LYL1 function by showing that it is required also for the formation of the endothelial barrier specifically in mature lungs by acting upstream of VE-cadherin and of RhoA.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…We previously reported that lack of LYL1 affects the maturation of newly formed blood vessels in adult mice and reduces active Rap1 in ECs (32). Here, we completed our analysis of LYL1 function by showing that it is required also for the formation of the endothelial barrier specifically in mature lungs by acting upstream of VE-cadherin and of RhoA.…”
Section: Discussionsupporting
confidence: 49%
“…We previously reported that LYL1 silencing in human ECs downregulate the expression of several molecules that contribute to endothelial junction maturation (32), namely integrin-␣2, which has an important role in EC-ECM attachment (6), as well as RapGEF1 and RapGEF2, which have multiple roles through Rap1 activation in AJ maturation (30). In this study, we show that LYL1 also regulates the activity of RhoA in ECs and that LYL1 downregulation leads to impaired AJs.…”
mentioning
confidence: 63%
See 3 more Smart Citations